2020
DOI: 10.3390/diagnostics10100847
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Left Superior Vena Cava with Absent Right Superior Vena Cava and Discrete Subaortic Stenosis Diagnosed in a Patient with Sick Sinus Syndrome: A Case Report and Brief Review of the Literature

Abstract: A persistent left superior vena cava (PLSVC) is the most frequent anomaly of the venous drainage system. While both a right and left superior vena cava (SVC) are usually present, a unique, left-sided SVC, also known as an isolated PLSVC, accounts for only 10–20% of cases. It is frequently associated with arrhythmias and other congenital cardiac anomalies. Though it is usually an asymptomatic condition, it may pose significant problems whenever central venous access is needed. We report a case of an isolated PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
0
17
0
2
Order By: Relevance
“…Another associated congenital anomaly, with stronger clinical implications, was described in a previously published case. In this case, the patient was also diagnosed with subvalvular aortic stenosis, determined by a subaortic membrane, which is a rare finding, with only few similar cases being reported in the literature [ 5 ]. It has been observed that patients with PLSVC can also present conduction disorders, which arise as a result of the histological abnormalities caused by the dilated coronary sinus [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another associated congenital anomaly, with stronger clinical implications, was described in a previously published case. In this case, the patient was also diagnosed with subvalvular aortic stenosis, determined by a subaortic membrane, which is a rare finding, with only few similar cases being reported in the literature [ 5 ]. It has been observed that patients with PLSVC can also present conduction disorders, which arise as a result of the histological abnormalities caused by the dilated coronary sinus [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these cases, we identified six patients who had PLSVC, which leads to an incidence of at least 0.15% of this anomaly in the group of patients who required implantable devices in our clinic. It should be mentioned that, in these cases, we met several types of this congenital anomaly (two cases of type II, two cases of type III A, and two cases of type III B according to Schummer’s classification); however, in this article, we will present only four cases, since two of them have already been published [ 5 , 6 ]. None of these patients met the criteria for cardiac resynchronization therapy.…”
Section: Case Reportsmentioning
confidence: 99%
“…However, as PLSVC is mostly asymptomatic, the actual prevalence of this anomaly might be underestimated. In association with congenital heart disease (CHD), the incidence is even higher, reaching 9 to 10% [ 3 , 9 ]. Reports regarding CHD and PLSVC vary, due to demographics and the clinical characteristics of the studied population.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent left superior vena cava (PLSVC) is the most common venous drainage anomaly of the systemic thoracic veins, with its prevalence among the general population ranging from 0.5 to 2%. In 80–90% of the cases, the PLSVC drains into the right atrium via a dilated coronary sinus [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…PLSVC is commonly associated with a normal right-sided superior vena cava. However, in 10–20% of cases, an isolated PLSVC may be present, frequently coexisting with other cardiac congenital disorders or arrhythmias [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%